Kingdom marriage eaudiobook Connecting god's purpose with your pleasure. - Evans, Tony (christianaudio, 2016)
What happens when a kingdom man marries a kingdom woman? Kingdom Marriage: Connecting God's Purpose with Your Pleasure helps couples grow together as a kingdom couple to fulfill God's design and purpose for their marriage. Through practical insights and powerful stories, Dr. Tony Evans inspires and instructs so couples will discover the hope, challenge, and guidance God's Word provides for their journey together. "You can reflect the glory of God and the unity of the Trinity through your shared purpose, honor, and love as a true kingdom couple." ?Tony EvansKingdom Marriage shows couples that the key to influencing our society and world with lasting impact is found in solidifying biblical marriage in the way God intended. It starts with both wife and husband reflecting God and His image and modeling that reflection within the roles and responsibilities of their union. This is based on a correct understanding of God's kingdom and their responsibilities in it.Kingdom Marriage and the Kingdom Marriage devotional and video resources are part of an entire line of Kingdom products by Tony Evans, including Kingdom Man, Kingdom Woman, Raising Kingdom Kids, and the Kingdom Quest strategy guides for kids and teens.